2020
DOI: 10.1186/s12913-020-4905-4
|View full text |Cite
|
Sign up to set email alerts
|

Development and psychometric evaluation of a questionnaire to measure cancer patients’ perception of care coordination

Abstract: Background: Although the importance of care coordination (CC) is well-recognized, cancer patients often receive poorly coordinated care across varied care settings and different oncology providers. Efforts to improve cancer care are hampered by lack of adequate measures. In this two-part, mixed-method study, we describe the development, refinement, and validation of a new care coordination instrument (CCI) designed to assess cancer patients' perception of CC. Methods: In Study 1, an initial CCI was developed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 43 publications
0
8
0
1
Order By: Relevance
“…Instrument development, field testing, and initial psychometric properties of the CCI were described in our prior study. 21 If the respondents had multiple oncology providers or received more than one intervention, they were asked to base their responses on what most commonly applied to them. This instrument assesses patients' perceptions of CC overall and three domains of CC: communication, navigation, and operational.…”
Section: Measurementioning
confidence: 99%
See 1 more Smart Citation
“…Instrument development, field testing, and initial psychometric properties of the CCI were described in our prior study. 21 If the respondents had multiple oncology providers or received more than one intervention, they were asked to base their responses on what most commonly applied to them. This instrument assesses patients' perceptions of CC overall and three domains of CC: communication, navigation, and operational.…”
Section: Measurementioning
confidence: 99%
“…20 The CCI measures patients' perceptions of CC overall and across three domains (communication, navigation, and operational) that are conceptualized as critical components of CC. 20 Although our prior work has established reliability and face and content validity of the instrument, 21 the utility of the revised CCI in a broad population of patients with cancer has not yet been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…O Atlas também foi referência na criação de um instrumento para avaliar, na perspectiva dos usuários, a coordenação do cuidado no tratamento de câncer nos Estados Unidos. O instrumento foi bem avaliado, sendo considerado uma alternativa para balizar estratégias de coordenação do cuidado 45 .…”
Section: Discussionunclassified
“…The CCI is a 29-item, multiple-choice self-report questionnaire designed to measure patients' perceptions of cancer CC both overall (total score) and across three domains of CC (Communication, Navigation, and Operational), with higher scores indicating better perceived CC. 34 This instrument has been used in other CC studies and has demonstrated excellent psychometric properties. [34][35][36] In addition to the CCI, a supplemental questionnaire was administered to CT participants.…”
Section: Methodsmentioning
confidence: 99%